Effect of Feed Concentration on the Production of Pregelatinized Starch in a Double Drum Dryer - S. Al-Mukhtar, Riyadh (Iraqi Journal of Chemical and Petroleum Engineering, 2007)
Double drum dryer is operated for producing pregelatinized maize starches using feed starch slurries of differentsolids(7, 10 and13 g/100 g )content . Steam pressure (2,3,and 4 bar), the level of pool between the drums (4,7,and 10cm) , and speed of drums rotation (3,4,and 6 rpm) are varied together with the feed solids content in a practical range ofvalues. The response of the dryer is registered by measuring several output variables, i.e. external drum temperature,product moisture content, mass flow rate.